Design and fabrication of a metastable β-type titanium alloy with ultralow elastic modulus and high strength - Guo, Shun; Meng, Qingkun; Zhao, Xinqing; Wei, Qiuming; Xu, Huibin (Scientific reports, 2015)
Titanium and its alloys have become the most attractive implant materials due to their high corrosion resistance, excellent biocompatibility and relatively low elastic modulus. However, the current Ti materials used for implant applications exhibit much higher Young’s modulus (50 ~ 120 GPa) than human bone (~30 GPa). This large mismatch in the elastic modulus between implant and human bone can lead to so-called “stress shielding effect” and eventual implant failure. Therefore, the development of β-type Ti alloys with modulus comparable to that of human bone has become an ever more pressing subject in the area of advanced biomedical materials. In this study, an attempt was made to produce a bone-compatible metastable β-type Ti alloy. By alloying and thermo-mechanical treatment, a metastable β-type Ti-33Nb-4Sn (wt. %) alloy with ultralow Young’s modulus (36 GPa, versus ~30 GPa for human bone) and high ultimate strength (853 MPa) was fabricated. We believe that this method can be applied to developing advanced metastable β-type titanium alloys for implant applications. Also, this approach can shed light on design and development of novel β-type titanium alloys with large elastic limit due to their high strength and low elastic modulus.